I Identifikasi Kadar Formalin Pada Tahu Mentah Yang Dijual Di Pasar Tradisional Kota Banjarmasin - Adinda Novita Sari; Rahmadani Rahmadani; Nur Hidayah (Jurnal Pelayanan Kefarmasian dan Sains, 2021)
Background : Tofu is one of the most famous consumed food in local society. But there still some naughty tofu sellers that using fotmalin in their tofu, as preservative. Although they obviously know that using formalin as food preservative can cause bad impact to human body. In short term effect causes nausea, vomitting, skin irritation, shortness breath and diarrhea. Beside, in long term effect causes cancer. Purpose : To know contain of formalin levels on raw tofu in traditional markets exceed the regulation. Also to know if there is an effect of sampling locations on levels of formalin in raw tofu. Method : Cross Sectional method is used in this research. People who sell tofu in Banjarmasin traditional markets were randomly selected as samples. Formalin levels analyed by using qualitative test with color reactor and quantitative test with Spectrophotometry UV-Vis. Result : In qualitative analysis with KMnO4 and Schiff , all sample shown positive result, except Sample 1. The test of using reactor KMnO4 has negative result on Sample 1. In quantitative analysis of formalin levels on Sample 1 is 13,182 mg/L, Sample 2 is 13,813 mg/L, and Sample 3 is 16,742 mg/L. In analysis tests, shown significant impact on the different markets to formalin levels in raw tofu. The result Ï value 0,006 shown strong impact and connected to different markets location to formalin levels in raw tofu. Conclusion : Result of formalin levels analysis on raw tofu shown the formalin was found in the tofu and has different markets location effect to formalin levels in raw tofu. Keyword : Raw Tofu, Formalin, Traditional Market, Spectrophotometry UV-Vis.